2018
DOI: 10.1002/adma.201802201
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Materials for Next‐Generation Spacecraft

Abstract: Spacecraft are expected to traverse enormous distances over long periods of time without an opportunity for maintenance, re‐fueling, or repair, and, for interplanetary probes, no on‐board crew to actively control the spacecraft configuration or flight path. Nevertheless, space technology has reached the stage when mining of space resources, space travel, and even colonization of other celestial bodies such as Mars and the Moon are being seriously considered. These ambitious aims call for spacecraft capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 112 publications
0
74
0
Order By: Relevance
“…For the selected electric motor, the different types of commercial batteries available were taken into account: Acid lead, NiMH, NiCd, LiPo, and LiFePO4, although new materials for batteries in aerospace and aeronautical applications will be available in the coming years [79][80][81]. However, with the actual state of technology and market prices, it was concluded that the best battery to be used in the electric ALO is the lithium polymer (LiPo) battery.…”
Section: New Electronic Power Systemmentioning
confidence: 99%
“…For the selected electric motor, the different types of commercial batteries available were taken into account: Acid lead, NiMH, NiCd, LiPo, and LiFePO4, although new materials for batteries in aerospace and aeronautical applications will be available in the coming years [79][80][81]. However, with the actual state of technology and market prices, it was concluded that the best battery to be used in the electric ALO is the lithium polymer (LiPo) battery.…”
Section: New Electronic Power Systemmentioning
confidence: 99%
“…Proponents of Mars colonization consider present space technology as nearing the stage when it will be able to provide the necessary level of reliability and efficiency required for the one way journey from Earth to Mars. Indeed, a recent example of successful firing of thrusters on Voyager 1 after 37 years of space operation attests to our ability to overcome such significant challenges of spacecraft development as longevity, reliability, and operational readiness decades after launching. Ongoing advances in nanotechnology and materials engineering enhanced reliability and expanded functionality of contemporary electronics and robotics while reducing device mass, volume, and power consumption .…”
Section: Mars Colonization—do We Need It?mentioning
confidence: 99%
“…[3][4][5] In recent decades, the space industry has demonstrated notable enthusiasm for small missions and ongoing advances in the manufacturing of space systems by small private companies, which take advantage of innovations made in other areas of science and technology. [6][7][8][9] As an outcome, more complex CubeSat and small satellite missions have been proposed, showing that CubeSats are transforming from being exclusively efficient systems to offer possibilities for broader space exploration. [6][7][8][9] As an outcome, more complex CubeSat and small satellite missions have been proposed, showing that CubeSats are transforming from being exclusively efficient systems to offer possibilities for broader space exploration.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, impels the improvement of small satellites of the CubeSat standard. [6][7][8][9] As an outcome, more complex CubeSat and small satellite missions have been proposed, showing that CubeSats are transforming from being exclusively efficient systems to offer possibilities for broader space exploration. [10,11] In spite of the noteworthy advancements made in CubeSat and the innovative work in the development of small satellites during the recent decade, some principal materials-related issues still remain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation